Transformations Of the Chinese Tourism Sector During the Coronavirus Pandemic - Mingliang Xiao; Mohammad Kamrul Alam (Communications of International Proceedings, 2021)
Before the outbreak of the epidemic crisis (COVID-19), tourism in China was high and flourishing. Tourism in China has always brought a lot of income to the economy of their state. During the coronavirus epidemic, the tourism business in China was very badly affected and, like in all other countries, it had to close all its borders and restrict the entry and exit of tourists. Because of this, the tourism business in China had to suffer very colossal losses. The coronavirus epidemic has forced all states in the world to reduce to a minimum travel to themselves and to other countries. Therefore, the tourism business and some other areas of commercial activity have greatly decreased and froze indefinitely. In connection with the intensified coronavirus epidemic, governments have adopted strict restrictions and introduced quarantines in many states. This especially happened during the holidays, the prohibition of students traveling abroad in order to avoid a large infection of the population in their countries. Nothing like this has ever existed in world practice, and such trips have never been limited very rigidly - so, in its message, the World Tourism Organization (UNWTO) defined [1]. The huge number of closed borders to many states in the world has brought very large losses in the billions of dollars in the tourism business. This is, first of all, due to missed trips and the loss of jobs in travel agencies and companies and the return of funds to failed tourists. The coronavirus epidemic has caused colossal losses in the entire international tourism business in the amount of 320 billion dollars in lost revenue for 2020 [2]. Thus, due to the pandemic around the world, the tourism business has become irrelevant and unprofitable. Today, a rapid rise in the tourism industry is unlikely as restrictions on international travel persist and demand for international travel remains low. However, there are still new opportunities for the development of tourism in China, which will be discussed in this article.
Keywords: Pandemic; Tourism; Travel Agency; Strategies; International Travel.